Hydrogen-bond acidity of ionic liquids: an extended scale - Kurnia, K.A. (Royal Society of Chemistry, 2015)
One of the main drawbacks comprising an appropriate selection of ionic liquids (ILs) for a target application is related to the lack of an extended and well-established polarity scale for these neoteric fluids. Albeit considerable progress has been made on identifying chemical structures and factors that influence the polarity of ILs, there still exists a high inconsistency in the experimental values reported by different authors. Furthermore, due to the extremely large number of possible ILs that can be synthesized, the experimental characterization of their polarity is a major limitation when envisaging the choice of an IL with a desired polarity. Therefore, it is of crucial relevance to develop correlation schemes and a priori predictive methods able to forecast the polarity of new (or not yet synthesized) fluids. In this context, and aiming at broadening the experimental polarity scale available for ILs, the solvatochromic Kamlet-Taft parameters of a broad range of bis(trifluoromethylsulfonyl)imide-(NTf2-)-based fluids were determined. The impact of the IL cation structure on the hydrogen-bond donating ability of the fluid was comprehensively addressed. Based on the large amount of novel experimental values obtained, we then evaluated COSMO-RS, COnductor-like Screening MOdel for Real Solvents, as an alternative tool to estimate the hydrogen-bond acidity of ILs. A three-parameter model based on the cation-anion interaction energies was found to adequately describe the experimental hydrogen-bond acidity or hydrogen-bond donating ability of ILs. The proposed three-parameter model is also shown to present a predictive capacity and to provide novel molecular-level insights into the chemical structure characteristics that influence the acidity of a given IL. It is shown that although the equimolar cation-anion hydrogen-bonding energies (EHB) play the major role, the electrostatic-misfit interactions (EMF) and van der Waals forces (EvdW) also contribute, admittedly in a lower extent, towards the hydrogen-bond acidity of ILs. The new extended scale provided for the hydrogen-bond acidity of ILs is of high value for the design of new ILs for task-specific applications. This journal is Â© the Owner Societies.